Pengaruh Pemberian Quadriceps Isometric Exercise Terhadap Peningkatan Fungsional Pada Pasien Osteoarthritis Genu Di Klinik Fisioterapi Kineta Sidoarjo - Laurentius Gigih Hari Utomo; Nurul Halimah; Agung Hadi Endaryanto; Fransisca Xaveria Hargiani (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: to find out the effect of quadriceps isometric exercise on functional improvement in patients with osteoarthritis genu  Methods: This study used the pre experimental of one group pre test and post test design, respondent numbered 30; men and women, data collection measurement of functional ability using WOMAC(Western Ontario and McMaster Universities). Normality test using paired T-test and continued with data analisis using Wilcoxon Results: in the functional measurements with WOMAC (Western Ontario and McMaster Universities) there was a functional increase in genu osteoarthritis patients after being given quadriceps isometric exercise, and the results of the hypothesis test with normality data distribution show significance value <0,005 Conclusion: Giving isometric quadriceps exercises has been shown to have an effect on functional improvement in genu osteoarthritis patients.